(untitled) (Trabalho & Educação, 2018)
The article aims to verify the influence of the work of the manager in the promotion of teacher welfare. It is a qualitative research, with a case study, contextualized in the Network of a city in the South of Brazil, with managers and teachers. The methodological procedures include literature review, documentary analysis and the application of an online questionnaire. Data analysis considers Bardin (2011). The results fall on: Status and Vocational Choice by the Teaching Profession; Legal Aspects; External groups; The Manager’s Role interferes in the Emotional, Physical and Intellectual Teacher welfare and the place of the Humanistic and Motivational Dimension of School Management in teaching. It is concluded that training for school management, in addition to legal and administrative aspects, includes elements of human and motivational training. ___ O artigo objetiva verificar a influência do trabalho do gestor na promoção do bem-estar docente. Trata-se de uma pesquisa qualitativa, tipo estudo de caso, contextualizada na Rede de um município do Sul do Brasil, com gestores e docentes. Os procedimentos metodológicos incluem revisão de literatura, análise documental e a aplicação de questionário on-line. A análise dos dados considera Bardin (2011). Os resultados recaem sobre: Status e Escolha Vocacional pela Profissão Docente; Aspectos Legais; Grupos Externos; O Papel do Gestor interfere no Bem-estar Emocional, Físico e Intelectual docente e o lugar da Dimensão Humanista e Motivacional da Gestão Escolar na docência. Conclui-se que a formação para a gestão escolar, muito além de aspectos legais e administrativos, inclui elementos de formação humana e motivacionais.